Disability Human Rights Law 2018 - Anna Arstein-Kerslake (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Disability human rights law is a rapidly growing field. It merges critical disability studies, disability rights, and human rights to inform, identify, analyse, and create solutions to help protect the human rights of people with disabilities. This is the second volume of the Disability Human Rights Law edited collection. This volume delves deeper into this emerging field and begins to explore what human rights law means for people with disabilities, as well as what innovations people with disabilities are bringing to the field of human rights law.